Preparation and Characterization of Au/ TiO2:CdS Thin Film as Photocatalysis for Degradation of MB Dye in Water - Mohamed, Zainb K.; Mutter, Mahdi M.; Khalil, Souad G. (Iraqi Journal of Physics, 2025)
In this work, gold/ titanium oxide: cadmium sulfide (Au/TiO₂:CdS) thin film nanocomposites as photocatalysts were synthesized using the sol-gel technique and deposited on glass substrates using the dipping method for the degradation of Methylene Blue (MB) dye in water. The CdS doping with TiO2 at ratios 1:1, 0.25, and 0.5 wt%. Au/TiO₂: CdS thin film characterization was achieved using X-ray diffraction (XRD), atomic force microscopy (AFM), Raman spectroscopy, field effect electron scanning microscopy (FESEM), and UV-Vis spectroscopy. The results of XRD showed that the obtained phase of TiO₂: CdS was cubic. The results of AFM showed that the distribution of grain sizes increased with increasing CdS concentration, as did the roughness and RMS. The FESEM results indicated that the particle size decreased from 58.68 nm to 22.24 nm as the concentration of CdS increased. Raman spectroscopy revealed that the TiO₂ peaks appear only at 1300 cm⁻¹ (B1g), 1600 cm⁻¹ (A1g), and 2000 cm⁻¹ (Eg). The optical properties were enhanced after the addition of CdS. The photocatalytic decomposition of Au/TiO₂: CdS thin films was investigated by the degradation of MB dye in water under ultraviolet (UV) light exposure. The results showed excellent photocatalytic performance after the addition of CdS.